LINE TRACER PENYORTIR BARANG DENGAN QR CODE SEBAGAI PENGENALAN POSISI TARGET - Putra, Wisnu Rahmat Dwi; Fauzi, Rizana; Ardias, Erwin; Subito, Mery; Indrajaya, Muhammad Aristo; Rahman, Yuli Asmi (Foristek, 2025)
Robotic-based sorting systems offer an innovative solution to enhance efficiency and accuracy in the logistics industry. This research aims to design and implement a robotic system capable of automatically sorting goods by integrating barcode scanning technology and line tracer navigation. The system is built using an Arduino Mega 2560 as the main controller and is equipped with Stepper motors, DC motors, mecanum wheels, a GM65 barcode scanner, and various supporting actuators.Experimental results show that the GM65 sensor can optimally read barcodes at distances ranging from 15 to 55 cm. The servo motor demonstrates an accuracy rate of over 98%, while the Stepper motor performs optimally at a minimum voltage of 9.0 V. Additionally, line sensor calibration yields a threshold range between 528 and 573, ensuring accurate line detection. The system also exhibits stable movement with consistent speed and minimal travel time variation, indicating efficient operational performance.By integrating these technologies, the developed robotic sorter system significantly improves productivity, accuracy, and reliability in automated goods sorting processes. The implementation of this system is expected to support automation in the logistics sector and provide a practical solution to distribution management challenges in the era of Industry 4.0.